Instruction differentiates the processing of temporal and spatial sequential patterns: evidence from slow wave activity in humans - Schubotz, Ricarda (Neuroscience letters, 1999)
Event-related potentials (ERPs) were recorded while subjects monitored a visually presented sequence of stimuli that provided information about both a temporal pattern (rhythm) and a spatial pattern, and responded to rhythmical or spatial deviants. A third task, which required the monitoring of the same sequence for screen flickers served as a perceptual baseline condition and controlled for response preparation effects. The monitoring of temporal and spatial sequential information elicited negative slow potentials (SPs) over distinct topographical areas. Thus, attention to the temporal and to the spatial domain of one and the same stimulus sequence are reflected by distinct ERP components, providing evidence for distinct cortical sources.